Nanosecond pulsed laser ablation of silicon—finite element simulation and experimental validation. (29th May 2019) - Zhang, Junjie; Zhao, Liang; Rosenkranz, Andreas; Song, Chengwei; Yan, Yongda; Sun, Tao
Abstract: In the present work, we perform finite element simulations to investigate the ablated surface morphology of silicon by nanosecond pulsed laser ablation using low laser fluences ranging from 14.92 to 23.21 J cm −2 . The utilized finite element model comprehensively considers the following aspects: (1) combined effects of thermal conduction, convection and radiation on heat conduction; (2) temperature-dependent material properties; (3) instantaneous update of the laser focus due to evaporation-induced surface recession for low laser fluences; and (4) spatial and temporal Gaussian energy distribution of the laser pulse. Experimental work using the same laser machining parameters compared to the conducted finite element simulations are carried out to validate the simulation results. Through the optimization of the laser machining parameters by 2D and 3D finite element simulations and the respective experimental validations for eliminating heat-affected zone and promoting forming accuracy, high accuracy aligned micro-grooves are fabricated on silicon with high anti-reflective properties in a wide range of wavelengths between 400 and 2000 nm. This is fairly comparable with the performance of similar silicon microstructures by femtosecond laser ablation. Consequently, the current work presents a way to fabricate precise surface microstructures with high anti-reflective properties on silicon at low cost by nanosecond pulsed laser ablation.